2018
DOI: 10.2460/ajvr.79.3.348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a syringe aspiration technique versus a mechanical suction technique and use of N-butylscopolammonium bromide on the quantity and quality of bronchoalveolar lavage fluid samples obtained from horses with the summer pasture endophenotype of equine asthma

Abstract: OBJECTIVE To evaluate the effect of 2 bronchoalveolar lavage (BAL) sampling techniques and the use of N-butylscopolammonium bromide (NBB) on the quantity and quality of BAL fluid (BALF) samples obtained from horses with the summer pasture endophenotype of equine asthma. ANIMALS 8 horses with the summer pasture endophenotype of equine asthma. PROCEDURES BAL was performed bilaterally (right and left lung sites) with a flexible videoendoscope passed through the left or right nasal passage. During lavage of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A study performed by Bowser et al (2018) evaluated the effect of manual (syringe) aspiration versus mechanical suction [ 30 ], showing a larger volume of BAL fluid recovered and a lower total red blood cell (RBC) count after manual aspiration compared with mechanical suction [ 31 ]. Corroborating this, erythrocytes were not detected in BAL fluid in our study, suggesting that the BAL procedure with manual aspiration is safe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study performed by Bowser et al (2018) evaluated the effect of manual (syringe) aspiration versus mechanical suction [ 30 ], showing a larger volume of BAL fluid recovered and a lower total red blood cell (RBC) count after manual aspiration compared with mechanical suction [ 31 ]. Corroborating this, erythrocytes were not detected in BAL fluid in our study, suggesting that the BAL procedure with manual aspiration is safe.…”
Section: Discussionmentioning
confidence: 99%
“…Orard et al (2016) studied the influence of BAL volume (250 mL versus 500 mL of saline) on cytological profiles, finding a lower total cell count and neutrophil percentage with the larger volume [29]. There was poor agreement between the findings when 250 mL or 500 mL of BAL solution was used for diagnosing inflammatory airway disease, with a similar proportion of horses being classified as healthy or having inflammatory airway disease [30]. Sweeney et al (1992) reported a higher percentage of neutrophils and a lower percentage of mast cells when a smaller volume (50 mL) was used compared with a larger volume (350 mL) [27].…”
Section: Volume Usedmentioning
confidence: 99%